Determinan Minat Berkarir Mahasiswa FEBI PTKIN Jawa Timur di Perbankan Syariah - Laila Nur Mahmudah; Irma Yuliani (Institut Agama Islam Negeri Ponorogo, 2024)
Introduction: The main objective of this research is to test and analyze the influence of perception, religiosity, financial rewards, job market considerations, and educational background on the career interest of FEBI PTKIN East Java students in sharia banking, as well as test and analyze differences in career interest between FEBI PTKIN East Java students in cities and regions. This research includes quantitative research. The population in this study were FEBI PTKIN East Java students, with 190 samples. Analysis in this study used SEM-PLS and Independent t Test. Based on the research that has been conducted, the analysis results show that perception, religiosity, financial rewards, job market considerations, and educational background have a positive and significant influence on students' career interest in Sharia banking. However, the results of different tests show no significant difference in career interest between students in cities and regions.